EXPERIMENTAL STUDY OF INDIVIDUAL THERMOLUMINESCENT DOSEMETERS PERFORMANCES FOR MEASURING THE DOSE EQUIVALENTS IN SKIN AND EYE LENS - E. N. Sheleenkova (Радиационная гигиена)
The article gives a comparative analysis of existing and newly developed thermoluminescent detectors DTG-4, TTLD-580, TLD-1011(TM) and DTVS-01 and dosemeters MKD-A and MKD-B for the purposes of individual dosimetric control of skin and eye lens exposure to radiation. The dependence of sensitivity of different thermoluminescent dosemeters, designed for dose equivalents measurements in skin and eye lens on the type (photons and ȕ-particles) and energy of radiation was determined experimentally. There are conclusions about the limits of applicability of existing detectors and dosemeters under different radiation exposure conditions. The article evaluates the possibility of different dosimeter use for specific radiation exposure conditions.